Exploring Motivational Message and Literary Themes in Little Women (2019): A Masovian Perspective - Sadewi, Nurfadillah; Syamsurrijal, Syamsurrijal (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the motivational themes and themes in Greta Gerwig's film, Little Women (2019), based on Louisa May Alcott's work, from a Maslowian perspective, focusing on how the adaptation of the novel relates to the interplay between power, desire, and masculinity, using Louisa May Alcott's experiences. Gerwig's adaptation also serves as a general example of using Maslow's hierarchy of needs in feminist novels. According to Maslow's theory, everyone has five needs: physiological, safety, social, esteem, and self-actualization. (Maslow, 2017). This provides a basis for analyzing motivation in the novel. The relationships and identities of each main character in "Little Women"—Meg, Jo, Beth, and Amy March—are shaped by their relationships and identitieswith one another. (Bragg, 1978) This research analyzes the journey of human motivation portrayed in the film Little Women through the characters in their struggles to fulfil various types of human needs and the narrative. The method chosen to analyze this theory is qualitative, including text analysis, film analysis, character development, and dialogue to identify the actions and relationships of characters according to Maslow's hierarchy. The primary data source is the film Little Women (2019), directed by Greta Gerwig. Which has a duration of the film (2 hours 15 minutes) Specific elements analyzed include scenes that show the motivations and decisions of the characters. Dialog that reveals psychological and emotional needs. Symbolism, visual storytelling, and character interactions. Additional data includes academic literature on Maslow's theory and secondary sources that analyze the themes and characters of the film. The research findings indicate that the Maslovian perspective is a unique way to explain character evolution in detail and the importance of understanding the story, which can also be applied in psychology and sociology.